Brain changes associated with cognitive and emotional factors in chronic pain: A systematic review. (1st February 2017) - Malfliet, A.; Coppieters, I.; Van Wilgen, P.; Kregel, J.; De Pauw, R.; Dolphens, M.; Ickmans, K.
Abstract: An emerging technique in chronic pain research is MRI, which has led to the understanding that chronic pain patients display brain structure and function alterations. Many of these altered brain regions and networks are not just involved in pain processing, but also in other sensory and particularly cognitive tasks. Therefore, the next step is to investigate the relation between brain alterations and pain related cognitive and emotional factors. This review aims at providing an overview of the existing literature on this subject. Pubmed, Web of Science and Embase were searched for original research reports. Twenty eight eligible papers were included, with information on the association of brain alterations with pain catastrophizing, fear‐avoidance, anxiety and depressive symptoms. Methodological quality of eligible papers was checked by two independent researchers. Evidence on the direction of these associations is inconclusive. Pain catastrophizing is related to brain areas involved in pain processing, attention to pain, emotion and motor activity, and to reduced top‐down pain inhibition. In contrast to pain catastrophizing, evidence on anxiety and depressive symptoms shows no clear association with brain characteristics. However, all included cognitive or emotional factors showed significant associations with resting state fMRI data, providing that even at rest the brain reserves a certain activity for these pain‐related factors. Brain changes associated with illness perceptions, pain attention, attitudes and beliefs seem to receive less attention in literature. Significance: This review shows that maladaptive cognitive and emotional factors are associated with several brain regions involved in chronic pain. Targeting these factors in these patients might normalize specific brain alterations.